STRATEGIC MANAGEMENT OF INDUSTRIAL ENTERPRISES AND FORMATION OF HR SYSTEM IN THE CONTEXT OF THE DEVELOPMENT OF THE DIGITAL ECONOMY IN NETWORKS - Rajavaliyev Xurshidbek Maxamadsalimovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the use of the digital economy in the strategic management of industrial enterprises and the development of the HR system. It also analyzed the socio-economic mechanisms of strategic management of industrial enterprises and the formation of the HR system, identified its characteristics and existing problems.